Tinjauan Yuridis Tentang Konstruksi Tindak Pidana dalam Undang-Undang Informasi Transaksi Elektronik (ITE) Mengenai Pasal-Pasal Karet terhadap Pengaruh Impunitas Hukum - Fadly Mulyana Akbar; Anisa Nurhasanah; Ida Farida; Putri Kiki Lestari; Elsa Sakinah (International Forum of Researchers and Lecturers, 2024)
Problems regarding legal justice in cases spread across cyberspace have given rise to paradigm shifts and conflicts in viewing the application of a legal system or product as a means of buying and selling to achieve certain goals such as personal satisfaction which can be very detrimental to other parties. The main focus of improving the ITE Law must be on flexible articles, with the main aim of protecting freedom of opinion as a crucial element in the survival of democracy. Articles that are susceptible to multiple interpretations require proof and data support, especially regarding sanctions for creators and spreaders of hoaxes. Therefore, input from various parties is very necessary to fulfill people's aspirations and answer the nation's needs in the future. Criticism that is based on facts must be respected, while criticism that is slanderous and provocative must face legal consequences. The ITE Law is not aimed at curbing freedom of opinion, but rather at responding to the actions of creators and spreaders of hoaxes, slander and provocation in society. The government is concerned that undemocratic electronic information regulation could undermine national unity and give free rein to unethical content creation. In fact, there are parties who systematically produce and spread content that contains hatred, based on SARA, pornography, radicalism and terrorism through the use of robots, with motives that can be political or economic.